Comic Media to Improve Speaking Skill of the Fourth Grade Students - Nella Dwi Andini; Otang Kurniaman; Syahrilfuddin (Universitas Pendidikan Ganesha, 2022)
Comic media can improve students' speaking skills. The use of comic media that is suitable for child development can improve the learning quality and make it easier for learning objectives to be achieved quickly. In addition, students also gain experience in language, namely the addition of new vocabulary and improve speaking skills. The purpose of this research is to improve the speaking skills of the fourth grade elementary school students by using comic media that have met the eligibility criteria. This research is a development research with ADDIE method which includes five stages; Analysis, Design, Development, Implementation, and Evaluation. This study involving 3 validators, consist of a media expert, material expert, and language expert and in trial was carried out on 10 students. The process of data analysis including validity test, reliability test, normality test, and pair T-Test. Based on the results of the reliability test, before and after the obtained value of cronbanch's alpha is greater than the total correlated item and is declared reliable. information was obtained that the value of Sig. There is an increase in the average score after using comic media, meaning that there is an influence in the provision of comic media on students' speaking skills. It was concluded that comic media can improve students' speaking skills.